Selected issues of preventive activity in criminal proceedings - Dzyurbel, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article highlights the theoretical and practical issues of a special preventive function to combat crime, which is carried out by the investigator, investigator (detective), prosecutor and court (judge) within the pre-trial investigation and trial in criminal proceedings. Based on the analysis of the current legislation, in particular, the specific tasks established for law enforcement agencies to prevent criminal offenses and problems of practice, the need to supplement the Criminal Procedure Code of Ukraine with norms that would regulate the powers and procedure of the prosecution and the court (judge) in identifying the causes and conditions that made it possible for them to commit a criminal offense in the process of pre-trial investigation and trial. The views of scientists are analyzed and their own position on the expansion of the subject of proof in criminal proceedings, defined by Article 91 of the CPC of Ukraine, and the inclusion in its list of establishing the causes and conditions that concocted the commission of a criminal offense. It is concluded that the institution of the reasons and conditions that contributed to the commission of a criminal offense should be considered through the prism of law, and not the duty of the prosecution and the court (judge). The necessity of introducing into the CPC of Ukraine a number of articles that would authorize the prosecution, in the case of establishing the causes and conditions that made it possible to commit a criminal offense, has been substantiated, to submit to the relevant state body, public organization or official a submission on taking measures to eliminate these causes and conditions, and to the court (judge) - to make a separate ruling (decision).